The use of web-based digital media to develop oral literacy skills of elementary school students: systematic literature review - Ika Kurnia Setya Anggara; Wahyu Sukartiningsih; M. Bambang Edi Siswanto (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2026)
Oral literacy skills are fundamental competencies that elementary school students must master as a foundation for communication and lifelong learning. The development of digital technology opens new opportunities in language learning by integrating web-based media, increasing students' engagement, and improving the effectiveness of their speaking skill development. This study aims to systematically analyse the effectiveness of web-based digital media, particularly Google Sites and digital storytelling applications, in developing elementary school students' oral literacy skills. The systematic literature review method was used by analyzing 24 scientific articles published between 2020 and 2025 from trusted academic databases. Inclusion criteria include research that addresses web-based digital media, oral or spoken literacy skills, and learning contexts in primary schools. Data analysis was carried out thematically by identifying the patterns, advantages, limitations, and recommendations of each study. The results showed that digital storytelling media and web-based platforms were effective in improving students' speaking skills, with an average score increase of 15-35%, while integrating the Think Talk Write learning model with digital media was highly effective in developing social communication and collaboration. The discussion revealed that the successful implementation of digital media depends on proper instructional design, adequate technology support, and comprehensive teacher training. The conclusion of this study recommends the development of a web-based interactive digital platform that integrates constructivist pedagogical approaches to optimize oral literacy learning in primary schools.